An Overview of Plastic Money in India: Exploring the Impact of Plastic Money on Consumer Preferences (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The utilization of plastic money in India is in solid surge. In the middle of April-June 2011-12, the debit card spending ascended by 30% against Rs16,948 crore a year ago wherein platinum card spending has expanded by 45% contrasted with Rs8,065 crore a year ago, according to the information discharged by Reserve Bank of India. The dispersion of plastic money has expanded because of the way that saving money division has turned out to be more forceful. Besides, duplication of clients is an essential region of worry for the business which can overstate the quantity of dynamic clients. The present paper makes an endeavor to comprehend the eventual outcomes of retreat on plastic money industry and its effect on shopper inclinations. The paper appropriately examines the adequacy of the cards among the Indian shopper and the variables impacting the card decision. Essential information was gathered through a very much organized survey with the example size of 150 respondents in Jammu locale. Factors identified with socioeconomics, for example, age, wage level and occupation were chosen for the examination. The outcomes demonstrate that the clients are moving from debit card to check card more than couple of years. The investigation additionally uncovered that for practical saving money exchanges, banks are currently focusing on influencing their clients to move their debit card exchanges from ATM to Point of offer. Debit cards are very appealing to accommodation driven buyer markets. As banks investigate potential debit based faithfulness framework in this manner accommodation and control looking for purchasers discovered platinum cards as more alluring alternative. This card business relies upon extremely solid and secure technology and requires an exceptionally solid availability spine. The theme taken for the exploration is a current issue identified with the plastic and the inclination of clients towards various kinds of debit cards of various banks.